Open science precision medicine in Canada: Points to consider - Palmira Granados Moreno; Sarah E. Ali-Khan; Benjamin Capps; Timothy Caulfield; Damien Chalaud; Aled Edwards; E. Richard Gold; Vasiliki Rahimzadeh; Adrian Thorogood; Daniel Auld; Gabrielle Bertier; Felix Breden; et al. (FACETS, 2019)
Open science can significantly influence the development and translational process of precision medicine in Canada. Precision medicine presents a unique opportunity to improve disease prevention and healthcare, as well as to reduce health-related expenditures. However, the development of precision medicine also brings about economic challenges, such as costly development, high failure rates, and reduced market size in comparison with the traditional blockbuster drug development model. Open science, characterized by principles of open data sharing, fast dissemination of knowledge, cumulative research, and cooperation, presents a unique opportunity to address these economic challenges while also promoting the public good.